Program Pendidikan Vokasional Untuk Pengelolaan Sumber Daya Alam Di Wilayah Hadimulyo Timur - Alif Ilham Akbar Fatriansyah1; Aan Budianto; Dinda Salsa Dwi Febriany; Irfan Azhari; Jaenullah (Institut Agama Islam Ma’arif NU (IAIMNU) Metro Lampung, 2022)
Abstract This community service program was implemented in Hadimulyo Timur, a region characterized by underutilized household yards with significant potential for agricultural productivity. The main problem addressed was the limited use of these yards and the low value added to harvested products, affecting local economic resilience. The program aimed to empower the community by enhancing practical skills in yard management and post-harvest processing to increase economic benefits and food security. The theoretical framework was based on community-based vocational education and participatory action research (PAR), emphasizing active community involvement and skill acquisition tailored to local resources. The method involved participatory planning, training on sustainable yard cultivation techniques, product processing workshops, and ongoing field assistance. Results indicated improved yard utilization, formation of farmer groups, and development of value-added products such as herbal teas and snacks. These changes contributed to increased household income, strengthened social cohesion, and heightened awareness of sustainable resource management. The findings suggest that community-based vocational training supported by participatory approaches effectively fosters both economic empowerment and environmental stewardship in rural settings. Keywords: Vocational Education Program, Natural Resource Management